The Bern Early Recognition and Intervention Centre for mental crisis (FETZ Bern)—An 8‐year evaluation. Issue 3 (6th May 2021) - Michel, Chantal; Kaess, Michael; Flückiger, Rahel; Büetiger, Jessica R.; Schultze‐Lutter, Frauke; Schimmelmann, Benno G.; Gekle, Walter; Jandl, Martin; Hubl, Daniela; Kindler, Jochen
Abstract: Aim: Early detection of, and intervention for, psychosis during its prodromal phase has the potential to alter the course of the disease and has therefore become a major objective of modern clinical psychiatry. An increasing number of early detection and intervention services have been established in Europe and worldwide. This study aims to describe and evaluate an early detection and intervention service for children, adolescents and adults (FETZ Bern) aged from eight to 40 years with a population catchment area of 1.035 million in Bern, Switzerland. Methods: Routine demographic, diagnostic and service usage data were collected upon admission to the service. Using a retrospective, descriptive and naturalistic study design, data was analysed for different age groups (children, adolescents and adults) and where available, outcome data after 12 and 24 months was evaluated. Results: The FETZ Bern has received 827 referrals with full diagnostic data available for 353 patients. The majority of the assessed patients were young males. While 40% met criteria for a clinical high‐risk state of psychosis, 20% were diagnosed with fully manifest psychosis at time of admission, and another 40% had one or more non‐psychotic axis‐I diagnoses. Conclusions: The FETZ Bern is the first early detection centre worldwide assessing children aged younger than 12 years, as well as adolescents and young adults in one service. Given that developmental peculiarities are important in understanding and ultimately treating psychosis, the FETZ Bern, with its emphasis on developmental peculiarities, should be considered as a model for other similar services.